Frequency of Piroplasms Babesia microti and Cytauxzoon felis in Stray Cats from Northern Italy. (4th May 2014) - Spada, Eva; Proverbio, Daniela; Galluzzo, Paola; Perego, Roberta; Bagnagatti De Giorgi, Giada; Roggero, Nora; Caracappa, Santo
Abstract : Emerging diseases caused by piroplasms pose a health risk for man and other animals, and domestic cats have been proposed as potential reservoirs for some piroplasm infections. The aim of this study was to identify the frequency of the piroplasms Babesia microti and Cytauxzoon felis in stray cats from northern Italy and to identify possible risk factors associated with these infections. Blood samples from 260 stray cats enrolled in a trap-neuter-release (TNR) program in northern Italy were examined with conventional PCR for the presence of Babesia microti and Cytauxzoon felis DNA. No sample (0.0%) tested positive for C. felis, whilst B. microti DNA was detected in two samples (0.8%). Both infected cats were in good clinical condition and recovered well from the neutering surgery. One of these two cats had a triple coinfection with Babesia microti, Candidatus Mycoplasma haemominutum, and Anaplasma phagocytophilum . Evidence presented in this study indicates that the blood borne protozoans Babesia microti and Cytauxzoon felis are not widely distributed in stray cat populations in Milan, northern Italy, and that the significance of cats as a reservoir host for B. microti in this area is limited.